2008
DOI: 10.1038/nsmb.1519
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into RNA recognition by the alternative-splicing regulator muscleblind-like MBNL1

Abstract: Muscleblind-like (MBNL) proteins, regulators of developmentally programmed alternative splicing, harbor tandem CCCH zinc-finger (ZnF) domains that target pre-mRNAs containing YGCU(U/G)Y sequence elements (where Y is a pyrimidine). In myotonic dystrophy, reduced levels of MBNL proteins lead to aberrant alternative splicing of a subset of pre-mRNAs. The crystal structure of MBNL1 ZnF3/4 bound to r(CGCUGU) establishes that both ZnF3 and ZnF4 target GC steps, with site-specific recognition mediated by a network of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
218
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(241 citation statements)
references
References 40 publications
18
218
3
2
Order By: Relevance
“…In particular, the C-terminal ZnK2 masks the conserved aromatic residue (Y) at the fifth position of RNP1. Although these conserved ZnK motifs mask the putative RNA binding surface of the U2AF 23 , and by analogy, U2AF 35 UHMs, the ZnK family typically interacts with RNA (e.g., Hudson et al 2004;Teplova and Patel 2008). Approximately 10% of MDS-patients harbor acquired mutations of the U2AF1 gene that encodes the U2AF 35 splicing factor (for review, see Inoue et al 2016).…”
Section: Do Uhms Bind Rna?mentioning
confidence: 99%
“…In particular, the C-terminal ZnK2 masks the conserved aromatic residue (Y) at the fifth position of RNP1. Although these conserved ZnK motifs mask the putative RNA binding surface of the U2AF 23 , and by analogy, U2AF 35 UHMs, the ZnK family typically interacts with RNA (e.g., Hudson et al 2004;Teplova and Patel 2008). Approximately 10% of MDS-patients harbor acquired mutations of the U2AF1 gene that encodes the U2AF 35 splicing factor (for review, see Inoue et al 2016).…”
Section: Do Uhms Bind Rna?mentioning
confidence: 99%
“…The function of the ZnFs lies in the specific binding of GC dinucleotides contained in single-stranded RNA. 33,34 Edge et al 35 reported that MBNL1 is remarkably tolerant towards mutations in individual ZnFs, but mutations of ZnF1 and 2 are highly deleterious. The reported variant is known in public databases as rs185894411 with a minor allele frequency of 0.004%.…”
Section: Discussionmentioning
confidence: 99%
“…The variant described here is located between the second and third cysteine in a 3 10 -helix element. 33 In a 3D model of the first two ZnFs created with the SWISS-MODEL, 36 based on the known crystal structure of MBNL1 tandem ZF1 and 2 domain (PDB: 3D2N 33 ), the wild-type and variant containing p.(Thr32Met) were compared. Two alterations were visible: a shift in the shape of the protein due to the exchanged AA residue on protein position 32 and a change in the hydrophobicity of the region (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of Muscleblind (Mbl) zinc finger domains to CUG repeats is strongly directed by the presence of aromatic residues (28). The sequence of the ABP1 hexapeptide is also enriched in aromatic amino acids.…”
Section: Abp1 Bound To Cug Repeats In Vitro Without Displacing Musclementioning
confidence: 99%
“…Interestingly, ABP1 has two aromatic amino acids in its sequence (tryptophan and tyrosine). The side chains of aromatic amino acids in a number of proteins have been found to be critical for enabling RNA binding, including the CCCH-type zinc finger protein Tis11, and MBNL1 (28,32).…”
Section: Abp1 Reversed Missplicing and Muscle Histopathology In A Dm1mentioning
confidence: 99%